Effect of Gamma Rays on some Yield Parameters and Protein Content of Soybean in M2, M3 and M4 Generation - D. Dhanavel, P. Pavadai, M. Girija and (Journal of Experimental Sciences, 2010)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> ABSTRACT: The effectiveness and efficiency, yield parameters and statistical analysis for M2, M3 and M4 generation of Soybean (Glycine max (L.) Merr.) using gamma rays treatment. Effectiveness and efficiency was recorded at increase for low concentration and decrease for high concentration level. The most of the treatment was positive shift was recorded. The statistical analysis such as variability, heritability and genetic advance as per cent of mean was recorded in high for treatment than the untreated plants for all the generation. 50KR of gamma rays treatment was effective than the other mutagenic treatments compared to control. Key words: Soybean, Mutation, Effectiveness, Efficiency, Frequency --- Department of Botany, Annamalai University, Annamalai Nagar – 608 002, Tamil Nadu, India --- Please Cite This Article As: P. Pavadai, M. Girija and D. Dhanavel. 2010. Effect of Gamma Rays on some Yield Parameters and Protein Content of Soybean in M2, M3 and M4 Generation. J. Exp. Sci. 1(6):08-11.